How to measure gymnast upper body relative strength on still rings with a pair of strain gauges - Lecocq, T.; Gouelle, A.; Tordi, N. (Science of Gymnastics Journal, 2025)
Over the last few decades, the development of the Code of Points, which defines the values for each gymnastic skill as well as possible errors, has brought with it the ubiquitous need for strength and hold elements (Group II) and Swing to strength hold elements (Group III) in order to be competitive on the still rings. This apparatus will be crucial in the upcoming Olympic cycle, therefor it's important to keep a close eye on gymnasts` progress. Despite being the gold standard, force plates are a costly and unwieldy piece of equipment for a federation interested in measuring strength. The purpose of this article is to determine how accurately the vertical component of the force produced by the gymnast (vForce) can be estimated using two strain gauges placed in the cables. 16 recreational gymnasts (32±11 years old, 74±7 kg, 173±6 cm) performed one maximal isometric contraction in the iron cross position. The tension in the cables were measured with a pair of strain gauges, while the vertical ground reaction force (vGRF) was recorded synchronously with a pair of force plates placed under the gymnast. The residuals of the tension are strongly correlated with the cable angle (R = 0.84), while the calculated vForce is completely uncorrelated with the cable angle (R = -0.09) and has a smaller systematic and random error (Bias ± LOA Range: -4.8N ± 13.3N). Strain gauges are valid instruments for measuring and monitoring the relative upper body force of gymnasts, provided that the cable angle is known and does not change during contraction.